Effectiveness of Etanol Extract Bajakah Wood (Spatholobus sp.) on the Growth of Staphylococcus aureus ATCC 25923 - Banjarnahor, Rifanny Paruma (Diponegoro International Medical Journal, 2024)
Background: Infectious diseases are still an important issue for Indonesia. One of the opportunistic bacteria that causes various infectious diseases is Staphylococcus aureus. There is a need for new alternative treatments that have the same high potential as antibiotics. Bajakah wood (Spatholobus sp.) is a plant that grows abundantly in the tropical forests of Central Kalimantan. This plant has the potential antibacterial potential because it contains secondary metabolite compounds, namely alkaloids, tannins and glycosides.Objective: This study aims to determine the effectiveness of Bajakah wood (Spatholobus sp.) on the growth of S. aureus ATCC 25923 bacteria through antimicrobe sensitivity test.Methods: In this study, three different methods were used, the disc method, the well method and the Whatman paper method using a concentration of 5%; 15%; 25%; 50% and 100% extract.Results: The results showed that the ethanol extract of Bajakah Wood (Spatholobus sp.) had antibacterial activity against S. aureus ATCC 25923 at the lowest concentration, namely 5%. The disk method obtained an average inhibition zone of 11.1 mm, the well method obtained an average inhibition zone of 16.8 mm and the Whatman paper method obtained an average inhibition zone of 10.8 mm.Conclusion: From this study, the ethanol extract of Bajakah wood (Spatholobus sp.) has antibacterial potential against S. aureus bacteria with its secondary metabolite compounds.